Soapstone in Northern Norway: archaeological and geological evidence, quarry and artifact survey results. - Wickler, Stephen; Lindahl, Ingvar; Nilsson, Lars Petter (University of Bergen, 2017)
Chapter from Hansen, G., Storemyr, P. (eds.). (2017) Soapstone in the North. Quarries, Products and People. 7000 BC - AD 1700. UBAS. ISBN: 978-82-90273-90-8. Archaeological research on the extraction, distribution and utilization of soapstone artifacts in northern Norway has been limited, but systematic geological documentation of soapstone exposures that includes quarry activity provides an opportunity to expand archaeological insights into soapstone provenance and extraction. This article brings together geological and archaeological evidence related to soapstone use in northern Norway to the north of Saltfjellet in Nordland in order to evaluate the current state of knowledge for this resource. The initial section provides a chronological overview of archaeological evidence for soapstone use and associated site contexts, including the distribution of artifact types in time and space. This is followed by a presentation of soapstone geology from a historical perspective focusing on quarry documentation. Quarry evidence is reviewed and results from recent collaborative geological and archaeological surveys presented within a framework of relevant research problems. The final section outlines potential avenues for future interdisciplinary soapstone research.